Combining doxorubicin-nanobubbles and shockwaves for anaplastic thyroid cancer treatment: preclinical study in a xenograft mouse model. Issue 6 (June 2017) - Marano, Francesca; Frairia, Roberto; Rinella, Letizia; Argenziano, Monica; Bussolati, Benedetta; Grange, Cristina; Mastrocola, Raffaella; Castellano, Isabella; Berta, Laura; Cavalli, Roberta; Catalano, Maria Graziella
Abstract : Anaplastic thyroid cancer is one of the most lethal diseases, and a curative therapy does not exist. Doxorubicin, the only drug approved for anaplastic thyroid cancer treatment, has a very low response rate and causes numerous side effects among which cardiotoxicity is the most prominent. Thus, doxorubicin delivery to the tumor site could be an import goal aimed to improve the drug efficacy and to reduce its systemic side effects. We recently reported that, in human anaplastic thyroid cancer cell lines, combining doxorubicin-loaded nanobubbles with extracorporeal shock waves, acoustic waves used in lithotripsy and orthopedics without side effects, increased the intracellular drug content and in vitro cytotoxicity. In the present study, we tested the efficacy of this treatment on a human anaplastic thyroid cancer xenograft mouse model. After 21 days, the combined treatment determined the greatest drug accumulation in tumors with consequent reduction of tumor volume and weight, and an extension of the tumor doubling time. Mechanistically, the treatment induced tumor apoptosis and decreased cell proliferation. Finally, although doxorubicin caused the increase of fibrosis markers and oxidative stress in animal hearts, loading doxorubicin into nanobubbles avoided these effects preventing heart damage. The improvement of doxorubicin anti-tumor effects together with the prevention of heart damage suggests that the combination of doxorubicin-loaded nanobubbles with extracorporeal shock waves might be a promising drug delivery system for anaplastic thyroid cancer treatment.